Conceptual Metaphor Analysis of "Feeling" Based on Corpus Data Among Depression Patients: (Analisis Metafora Konseptual "Rasa" Berasaskan Data Korpus dalam Kalangan Pesakit Kemurungan) (Jurnal Bahasa, 2021)
This study examines the phenomenon of depression in Major Depressive Disorder (MDD) patients from a language perspective. The research design is based on a case study of an MDD patient at the University of Malaya Medical Center (UMMC). The study used the Conceptual Metaphor Theory (CMT) by Lakoff and Johnson (1980), systematic metaphor analysis by Cameron et al. (2010), and Metaphor Identification Procedure (MIP) by Pragglejaz Group (2007). By building this study's own corpus data (i.e., DIY corpus), spoken data were transcribed for in-depth analysis. This study found that 61% of the word "feel" in the corpus data demonstrated a summation of a person's emotional language and feelings. Therefore, the word "feel" in the corpus data is analysed to ascertain how MDD patients implicitly express sadness, disappointment, and hopelessness. As many as 87% of linguistic metaphors were a realisation to the conceptualisation of depression. The findings also indicated that the Malay language is composed of a set of metaphors that are congruent with previous studies, whereby the identified metaphor of depression is highly relevant to the existing conceptual metaphor mapping, namely: DEPRESSION IS DOWN, DEPRESSION IS A PHYSICAL SYMPTOM, DEPRESSION IS A THING, DEPRESSION IS A BURDEN, DEPRESSION IS A LIVING ORGANISM, DEPRESSION IS A JOURNEY and DEPRESSION IS WAR. The combination of systematic metaphors can also frame the thinking of depressed patients and the surrounding community, forming a set of systematic metaphors, namely: MENTALLY ILL PATIENT’S PERCEPTION OF SOCIETY'S STIGMA IS A NEGATIVE PERCEPTION OF ISLAM.